Integrating Social Development and Financial Sustainability: The Challenges of Rural Computer Kiosks in Kerala - Renee Kuriyan, Kentaro Toyama, and Isha Ray
This paper examines the social and political challenges related to the implementation of information and communication technology (ICT) kiosk projects for rural development in India. Specifically, the paper focuses on the Akshaya project, a franchise of rural computer-service kiosks, which was implemented in Kerala as a public-private sector collaboration. The Akshaya project has the twin goals of social development through increased access to computers for rural people and financial viability through market-driven entrepreneurship. Using interview and participant observation methods, we examine the challenges that state actors and entrepreneurs face in simultaneously addressing social and financial sustainability. The preliminary evidence suggests that there is a tension between these goals at a macro level (within the state) and a micro level (for entrepreneurs and potential consumers) that makes it difficult to run a financially selfsustaining ICT kiosk project that also meets social development goals. The paper demonstrates that the implementation of ICTs for development is not simply a technical process of delivering services to the poor, but is a highly political process that involves tradeoffs and prioritization of particular goals to attain sustainability. Branding this project is a challenge for the state and entrepreneurs due to consumer perceptions of what development is, with particular expectations of state provided services, versus what business is.